دور تكنولوجيا المعلومات والاتصال في زيادة فعالية وسائل ترقية المبيعات -دراسة حالة مؤسسة كوندور الكترونيكس - Ben ahssen, Nassireddine; hamloui, Hamid (Finance and Business Economies Review, 2017)
The main aim of treating such topic is to know the extent exploitation of the -condor electronics- corporation of information and communication technology in order to raise up the effectiveness of the means of sales promotion directed to distributers. So the study sample included 25 distributers that are found in the towns of the country. And to measure the study variables, the researcher used the style of interview by phone to gather data. And to know the role of information and communication technology and to evaluate the effectiveness of the means of sales promotion in the line directed to consumers, the researcher analyzed the sales of the institution-condor electronics- during the five consecutive semesters.